Fenomen europejskich dżihadystów - Pasamonik, Barbara (Zakład Edukacji Międzykulturowej i Badań nad Wsparciem Społecznym Wydziału Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, 2016)
Radicalization under the banner of the Islamic State is not an exclusive domain of the Muslims from the Middle East, or even Muslims as such. On the territory of Syria and Iraq there are over thirty thousand of foreign fighters from eighty-six countries, including five thousand Europeans. The latter group embraces both the representatives of the second and third generation of the European Muslims, as well as the Western, Islamic proselytes, members of the middle, lower and upper class, both young men and women. Such a variety of the European jihadists demands the recognition of the multitude of causes and patterns of the radicalization of the young Europeans. Understanding of the phenomenon and popularity of the radical ideology of jihadism also calls for investigation of the social, cultural, and economic conditioning of this process. Moreover, the recent terrorist attacks in Paris and Brussels prove there is a reason for the European countries to fret the return of the seasoned radical fighters.
Keywords: European jihadists; islamic state; radicalization; Salafism; sect; terrorism